Two new species of Antillorena Jocqué 1991 from northeastern Brazil (Araneae, Zodariidae) - Brescovit, Antonio Domingos; Ruiz, Gustavo Rodrigo Sanches (Zootaxa, 2011)
The genus Antillorena Jocqué, 1991 proposed to include a single species from Lesser Antilles, is recorded for the first time from Brazil. Two new species are described from the state of Bahia, Brazil, namely Antillorena patapata sp. nov. and Antillorena gaia sp. nov.